2007
DOI: 10.1007/s10597-007-9104-9
|View full text |Cite
|
Sign up to set email alerts
|

Front Line Workers’ Attitudes towards Psychiatric Advance Directives

Abstract: Studies have begun to explore provider attitudes' toward psychiatric advance directives (PADs) and how those attitudes are related to provider characteristics. The study gathered attitudinal data from a sample of 193 social workers serving mentally ill adults. Social workers with pro-healthcare power of attorney (HCPA) attitudes were likely to have prior experience with an HCPA and to believe that involuntary treatment violates the NASW Code of Ethics. Social workers are more favorable of HCPAs than advance in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 27 publications
2
17
0
Order By: Relevance
“…However, the effect of value criteria on choosing specific options may be of interest beyond the limited set of options selected within the context of this study. For example, one important issue discussed in the literature about PADs is their possible legally binding status, the liability of clinicians to honour the statements, and the definition of conditions for overriding them (Atkinson et al 2003a;Van Dorn et al, 2006), particularly for proscriptive PADs Kim et al 2008;Swanson et al 2007). Although the legal status of the document was not discussed in our study, our results indicate that options for designing a PAD intervention should be driven by the enhancement of user autonomy, which might, in some contexts, mean making the PAD document legally enforceable.…”
Section: Main Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the effect of value criteria on choosing specific options may be of interest beyond the limited set of options selected within the context of this study. For example, one important issue discussed in the literature about PADs is their possible legally binding status, the liability of clinicians to honour the statements, and the definition of conditions for overriding them (Atkinson et al 2003a;Van Dorn et al, 2006), particularly for proscriptive PADs Kim et al 2008;Swanson et al 2007). Although the legal status of the document was not discussed in our study, our results indicate that options for designing a PAD intervention should be driven by the enhancement of user autonomy, which might, in some contexts, mean making the PAD document legally enforceable.…”
Section: Main Findingsmentioning
confidence: 99%
“…It is centred on a document in which the user notifies his/her preferences for treatment and may appoint a surrogate decision-maker for the period of incompetence (Atkinson et al 2004;Atkinson 2007;Campbell and Kisely 2009). PADs should contribute to numerous clinical and organisational aims in psychiatric care, including empowerment of the user and recovery Szmukler 2007), improving compliance with treatment (Swanson et al 2000; Thomas and Cahill 2004), continuity of care , and therapeutic alliance (Kim et al 2008; Thornicroft et al 2011;Van Dorn et al 2008); they should also eventually contribute to reducing the number of voluntary and involuntary hospitalisations (Henderson et al 2004). However, with the exception of the last study cited, randomised clinical evaluations have had disappointing results, showing little or no significant differences between intervention and control groups for primary outcomes (Borschmann et al 2013;Campbell and Kisely 2009;Papageorgiou et al 2002;Thornicroft et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence also suggests they have the potential to reduce coercive treatment (Henderson et al 2004;Swanson et al 2008), lead to discussions between consumers and outpatient clinicians that enhance the therapeutic relationship (Swanson et al 2006) and provide emergency room and inpatient clinicians with valuable information about what has or has not worked for a consumer before, and what treatment they will accept (Srebnik et al 2005;Strauss et al 2007;Srebnik and Russo 2007). However, there is also substantial evidence that implementation of advance directives for mental health care is difficult, including low rates of uptake (Swanson et al 2006) (except during research interventions); providers' reservations about their legal status and the implications of following treatment preferences with which they disagree (Swanson et al 2003;Kim et al 2007;Van Dorn et al 2006;Elbogen et al 2006;Atkinson et al 2004); inconsistent trial data regarding their effectiveness with respect to involuntary hospitalisation (Henderson et al 2004;Papageorgiou et al 2002;Swanson et al 2008Swanson et al , 2006; and low rates of access following completion (Srebnik and Russo 2007). These problems apply equally to directives for end of life care (SUPPORT Principal Investigators 1995;Annas 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The standards of the federal Center for Medicare and Medicaid Services (CMS) require that providers seeking reimbursement from those sources respect valid advance health care directives. The Duke studies indicated that health care professionals are generally accepting of the idea of advance directives, but are often unsure of how the law and ethical codes might constrain their use (Elbogen et al 2006;Van Dorn et al 2008;Kim et al 2008) In principle, there is no dispute that people's interests are served when they gain a degree of control over what happens at times when they cannot make legally competent decisions. In practice, it is unclear how much control advance psychiatric directives really provide.…”
Section: Psychiatric Advance Directives Relapse Prevention Recoverymentioning
confidence: 99%